DNA Quantity and Quality in Remnants of Traffic-Killed Specimens of an Endangered Longhorn Beetle: A Comparison of Different Methods. Issue 1 (18th August 2015) - Rusterholz, Hans-Peter; Ursenbacher, Sylvain; Coray, Armin; Weibel, Urs; Baur, Bruno
Abstract : The sampling of living insects should be avoided in highly endangered species when the sampling would further increase the risk of population extinction. Nonlethal sampling (wing clips or leg removals) can be an alternative to obtain DNA of individuals for population genetic studies. However, nonlethal sampling may not be possible for all insect species. We examined whether remnants of traffic-killed specimens of the endangered and protected flighless longhorn beetle Iberodorcadion fuliginator (L., 1758) can be used as a resource for population genetic analyses. Using insect fragments of traffic-killed specimens collected over 15 yr, we determined the most efficient DNA extraction method in relation to the state of the specimens (crushed, fragment, or intact), preservation (dried, airtight, or in ethanol), storage duration, and weight of the sample by assessing the quantity and quality of genomic DNA. A modified cetyltrimethyl ammonium bromide method provided the highest recovery rate of genomic DNA and the largest yield and highest quality of DNA. We further used traffic-killed specimens to evaluate two DNA amplification techniques (quantitative polymerase chain reaction [qPCR] and microsatellites). Both qPCR and microsatellites revealed successful DNA amplification in all degraded specimens or beetle fragments examined. However, relative qPCR concentration and peak height of microsatellites were affected by the state of specimen and storage duration but not by specimen weight. Our investigation demonstrates that degraded remnants of traffic-killed beetle specimens can serve as a source of high-quality genomic DNA, which allows to address conservation genetic issues.